Analisis Kesalahan Mahasiswa Pendidikan Matematika Universitas Negeri Medan dalam Menegasikan Definisi Limit Fungsi - Eka Finanti Septiana Simamora; Imel Simanungkalit; Nurcahaya Br Zandroto; Putri Br Tarigan; Michael Cristian Simanullang (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to identify students' errors in negating the definition of function limits using the Newman Error Analysis (NEA) approach. The method used is descriptive qualitative, with three selected students from one class totaling 32 people through a purposive sampling technique. Data were obtained from students' written answers to the problem of negating the definition of function limits. The results of the analysis show that students make various types of errors, such as transformation errors, understanding errors, reading errors, process skill errors, and coding errors. These errors reflect students' weak understanding of formal logic structures and the use of symbols in the context of mathematics, especially in the negation process which requires a deep understanding of the meaning of quantifiers and empowerment. This conclusion emphasizes the importance of strengthening mathematics learning and teaching strategies that emphasize conceptual understanding, not just procedural. In addition, learning evaluations need to be designed to explore students' thinking processes more thoroughly in order to accurately identify sources of errors.